Molecular epidemiology and genotype distributions of noroviruses and sapoviruses in Thailand 2000-2016: A review - Kattareeya Kumthip (2018)
© 2018 Wiley Periodicals, Inc. Norovirus (NoV) and sapovirus (SaV) infections remain public health problems in Thailand, particularly, causing an acute gastroenteritis in people of all age groups. This review summarizes the epidemiology and genotype distribution of NoV and SaV in Thailand during the period of 2000-2016. The overall prevalence of NoV infection in patients with acute gastroenteritis of all age groups ranged from 0.09% to 44.7% while those of SaV were 0.0-15.0%. The majority of NoV genogroup detected was NoV GII with a small proportion of NoV GI. The NoV GII.4 was the most predominant genotype (63.4%) followed by GII.3 (15.0%), GII.6 (3.9%), GII.17 (3.3%), GII.13 (2.1%) and many other genotypes with small proportion. Furthermore, eight GII.4 variant strains and 11 different NoV recombinant strains had also been reported. For SaV, 10 different human SaV genotypes were detected including GI.1, GI.2, GI.4, GI.5, GII.1, GII.2, GII.3, GII.4, GIV.1, and GV.1.